Long-term results of thoracoscopic ablation of paroxysmal atrial fibrillation: is the glass half full or half empty?. (29th March 2021) - Belluschi, Igor; Lapenna, Elisabetta; Carino, Davide; Trumello, Cinzia; Cireddu, Manuela; Ruggeri, Stefania; Schiavi, Davide; Monaco, Fabrizio; Pozzoli, Alberto; Agricola, Eustachio; Alfieri, Ottavio; De Bonis, Michele; et al.
Abstract:  : OBJECTIVES: Previous series showed the outcomes of thoracoscopic ablation of stand-alone symptomatic paroxysmal atrial fibrillation (AF) for up to 7 years of follow-up. The goal of this study was to assess the long-term durability of surgical pulmonary vein isolation (PVI) beyond 7 years. METHODS: Fifty consecutive patients {mean age 55 [standard deviation (SD): 11.2] years, previous catheter ablation in 56%, left ventricular ejection fraction 60% (SD: 4.6), left atrium volume 65 ml (SD: 17)} with stand-alone symptomatic paroxysmal AF underwent PVI through bilateral thoracoscopy ablation between 2005 and 2014. The CHA2 DS2 -VASc score was ≥2 in 12 patients (24%). RESULTS: No hospital deaths occurred. At hospital discharge all patients but 1 (2%) were in sinus rhythm (SR). Follow-up was 100% complete [mean 8.4 years (SD: 2.3), max 15]. The 8-year cumulative incidence function of AF recurrence, with death as a competing risk, on or off class I/III antiarrhythmic drugs (AADs)/electrocardioversion/re-transcatheter ablation (TCA) was 20% (SD: 5; 95% confidence interval: 10, 32); and off class I/III AADs/electrocardioversion/re-TCA was 52% (SD: 7; 95% confidence interval: 0.83, 8.02). At 8 years, the predicted prevalence of patients in SR was 87% and 53% were off class I/III AADs/electrocardioversion/re-TCA. The recurrent arrhythmia was AF in all patients except 2, who had atypical atrial flutter (4%). No predictors of AF recurrence were identified. At the last follow-up, 76% of the patients showed European Heart Rhythm Association class I. No strokes or thromboembolic events were documented and 76% of the subjects were off anticoagulation therapy. CONCLUSIONS: Despite a considerable AF recurrence rate, our single-centre, long-term outcome of surgical PVI showed encouraging data, with the majority of patients remaining in SR, although many of them were on antiarrhythmic therapy.